Fotodegradação do fungicida tiabendazol usando rejeitos industriais com propriedades magnéticas - Ferreira, Sandra Aparecida Duarte (2018)
The treatment of effluents from the agricultural industries is a subject of great environmental interest due to the impacts caused by inadequate management. Most often, the water used in post-harvest fruit washing accumulates toxic residues such as pesticides, herbicides, algicides, and fungal spores that are potentially polluting. In the papaya crop, the post-harvest fruits are treated in a tank containing fungicide syrup to control fungi that cause rot. This fruit wash effluent has a significant concentration of thiabendazole and can not be discarded in water bodies. The use of advanced oxidative processes (AOPs) appears as an alternative to conventional water treatment methods to reduce the impact caused by the use of the fungicide. The Fenton and photo-Fenton systems are highly efficient and low operational AOPs, widely used in the degradation of various pollutants such as pesticides, drug residues, hormones, dyes and others. The degradation of thiabendazole (TBZ) was evaluated by the solar heterogeneous photo-Fenton process with photocatalyst from particulate material (RMP), granite cutting residue (RBG) and Cu, Co, Mn and Ni ferrites. The catalysts were characterized by X - ray diffractometry (XRD), scanning electron microscopy (SEM) and inductively coupled plasma emission spectrometry (ICP OES). Sorting of the experimental factors was done with the RMP catalyst, in complete factorial design of type 23 with the variables: pH, mass of catalyst and [H2O2]. Only pH and [H2O2] significantly influenced the degradation of TBZ, monitored by UV-visible spectrophotometry at λ = 302 nm. The conditions of reactions under solar irradiation were: 20.0 mg of catalyst (0.7 gL-1 ), [H2O2] = 0.040 molL-1 and pH 3.0. The degradation efficiency with RMP, RBG and Cu ferrite at pH 3.0 reached levels of approximately 90% within 60 minutes of reaction. The Ni, Mn and Co ferrites present this percentage degradation in 90 minutes of reaction. The rate of photolysis with hydrogen peroxide reached degradation efficiency of 70% and 83% at 60 and 90 minutes, respectively. The performance of the photocatalysts were evaluated at pH 6.0 due to the proximity to the pH of the effluent. At this pH, the ferrite performance of Cu is highlighted, with 86% in 30 minutes of reaction. In 60 minutes, Cu and RBG ferrite presented 96% and 90% efficiency, respectively. The kinetic model of pseudo-first order was the one that most adjusted to the degradation of TBZ in the heterogeneous photo Fenton system, with the use of the photocatalysts studied. The stability of RMP after the fifth reaction cycle showed no loss in the degradation efficiency of TBZ. The decrease of COD in the papaya wash effluent, after photocatalytic treatment with RMP, was greater than 60%. The TBZ degradation by-products analyzed by ion chromatography reached 88.9% degradation, 79.0% in formic acid and 9.9% in acetic acid in 60 minutes of reaction with the RMP <270 catalyst. The use of RMP, RBG and Cu, Co, Mn and Ni ferrites by the heterogeneous photo-Fenton system with sunlight presents an efficient performance in TBZ degradation, which allows its use on a larger scale. The reuse of the RMP catalyst in five reaction cycles is advantageous due to its stability and ease of separation of the reaction medium by the application of a magnetic field. Combining effluent treatment with high degradation efficiency of pollutants to factors that reduce the cost of the process contributes to the reduction of the impacts caused by the launch of TBZ into environment.